2021
DOI: 10.1186/s12912-021-00632-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing student nurses’ clinical education in aged care homes: a qualitative study of challenges perceived by faculty staff

Abstract: Background Ageing populations are increasing the demand for geriatric care services. As nursing schools respond to this demand, more high-quality clinical placements are required, and aged care homes offer suitable placement sites. Although an aged care experience for students is beneficial, the basis for effective implementation of these placements is yet to be fully established. The aim of this study was to explore faculty staff perspectives on the challenges associated with providing effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…The unmet learning needs of students should drive changes in traditional practice placement models [ 15 , 37 ]. Our results provide evidence related to knowledge acquisition and meeting learning needs, which may justify the partial replacement of clinical hours in nursing homes by simulation training for first-year nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unmet learning needs of students should drive changes in traditional practice placement models [ 15 , 37 ]. Our results provide evidence related to knowledge acquisition and meeting learning needs, which may justify the partial replacement of clinical hours in nursing homes by simulation training for first-year nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…However, students’ access to supervision, feedback and quality learning experiences is not always optimal [ 11 , 12 ]. In nursing homes, the limited number of registered nurses that serve as supervisors can pose a significant challenge to the learning of first-year students who are just beginning their clinical experiences [ 13 15 ]. Prior studies have indicated that integrating simulation training as a partial replacement of clinical practice hours may improve learning [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researching student nurses' clinical placement studies in nursing homes helps to develop approaches to enhance students' learning experiences, stimulating their interest in caring for older people and encouraging them to view aged care as an attractive career option (Laugaland, Billett, et al, 2021, Laugaland, Kaldestad, et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…These goals are vital to meet the growing healthcare demands of an ageing population and the need for highly qualified nursing staff in nursing homes (Laugaland, Billett, et al, 2021, Laugaland, Kaldestad, et al, 2021. Therefore, university nursing programmes play a crucial role in developing and effectively utilizing clinical placements in nursing homes and preparing a workforce to meet future healthcare needs, especially those associated with an ageing population (Keeping-Burke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With aging populations and a rising demand for gerontology care services, this placement experience is an essential part of the curriculum, but is inevitably constrained by the positions available. As Laugaland et al ( 2021 ) note, low staffing levels of registered nurses (exacerbated by the ongoing Covid-19 pandemic) limit the capacity to effectively host students and can result in variation across a cohort’s learning experience, as well as a lack of quality assurance. In New Zealand, entry to aged residential care is available for all people over 65 who are assessed as needing it, on a means-tested, user-pays basis subsidised by public funding.…”
Section: Introductionmentioning
confidence: 99%